Delayed graduation and overeducation: A test of the human capital model versus the screening hypothesis - Carmen Aina; Francesco Pastore (Institute for the Study of Labor (IZA), 2012)
The academic circles are devoting a growing interest to delayed graduation and overeducation, but none has analyzed the joint consequences of these two phenomena. Thus, this paper studies the link between graduation not within the minimum period and overeducation, and the effects of these variables on wages, using the ISFOL-Plus data. According to the human capital model, delayed graduation increases a student' human capital and should, therefore, reduce her probability of being overeducated, while increasing her wage. According to the screening hypothesis, instead, delayed graduation signals low skills and therefore increases the chances of being overeducated, while bearing a wage penalty. The evidence lines towards predictions based on the screening hypothesis. First, delayed graduation increases the chances of overeducation. In addition, the direct wage penalty associated to delayed graduation equals 7% of the median wage. However, being a determinant of overeducation, it also indirectly contributes to the penalty of 19.8% of the median wage associated to overeducation. These effects are sizeable, considering the very low returns to higher education in Italy reported in previous studies.
urn:nbn:de:101:1-201206147274
Keywords: C25; C26; C33; I2; J13; J24; 330; university-to-work transition; delayed graduation; overeducation; human capital theory; screening hypothesis; earnings equations; Italy; Akademiker; Berufseinstieg; Unterbeschäftigung; Bildungsabschluss; Dauer; Signalling; Schätzung; Italien